Strategi Pemasaran yang Efektif dalam Meningkatkan Daya Saing UMKM di Jabodetabek - Masfar Gazali; Wiwik Robiatul Adawiyah; Khirstina Curry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This training aims to provide guidance on implementing effective marketing strategies to increase the competitiveness of MSMEs in the Jabodetabek area. The training participants are MSMEs and students who are members of the Bina Amanah Cordova Foundation. A more specific aim is to provide an understanding of Marketing Management for MSMEs and equip them with an understanding of effective Marketing Strategies for MSMEs. Before attending the training, around 75% of participants did not understand how to utilize marketing strategies in their business. Post-training evaluation shows that 100% of participants now understand how important it is to implement effective marketing strategies, especially by utilizing social media, which is currently one of the most popular trends in the marketing world.